The quality of life and body image disturbances of Turner syndrome patients in Malaysia: a cross-sectional study - Amirul Ashraf Bin Yusof; Manuela Lee Sze Chii; Nur Izzarizlyn Mohammad Yusoff; Raja Nur Iman Farhani Raja Mazrul Kama; Jairus Reuben Raj; Nur Azurah Abdul Ghani; Anizah Ali; Joyce Hong Soo Syn; Shamsul Azhar Shah; Nurkhairulnisa Abu Ishak; Adongo Susan Akinyi; Ani Amelia Zainuddin (BMC, 2023)
Abstract Background Turner Syndrome (TS) is a rare sex chromosome abnormality occurring in 1 in 2500 female live births. To date, there is limited data on TS patients in Malaysia. This study aimed to investigate the quality of life (QoL) and body image disturbances among adult population with TS in comparison to age-matched controls in a tertiary hospital in Kuala Lumpur: Hospital Chancellor Tuanku Mukhriz, Universiti Kebangsaan Malaysia (HCTM, UKM). Methods This was a cross-sectional study carried out in HCTM, UKM, Kuala Lumpur. TS participants who attended clinic in HCTM, UKM and controls who were hospital staff members were recruited via purposive sampling. TS participants' sociodemographic and clinical profiles were retrieved from medical records. Two validated, translated questionnaires; World Health Organization Quality of Life (WHOQOL-BREF) questionnaire and Body Image Disturbances Questionnaires (BIDQ) were completed by participants. Results A total of 34 TS patients were approached and 24 (70.5%) of them participated in this study. Their median (IQR) age was 24.0 (7.0) years and their responses were compared to 60 age-matched healthy females as controls [median age (IQR) = 24.0 (8.0) years]. The most common medical problem in TS participants was premature ovarian insufficiency (n = 23; 95.8%). There were no significant differences between TS and control groups' median scores (overall QOL; 4.00 vs. 4.00, general health; 3.50 vs. 4.00, physical health; 14.86 vs. 15.43, psychological health; 14.67 vs. 14.00 and environment; 15.00 vs. 15.50) of the different WHOQOL-BREF domains. However, TS participants were found to score 13.33 against 16.00, lower than the control group (p < 0.05) in the social relationship domain. Comparatively, body image concerns among TS respondents were significantly higher in impairment in the mainly social areas of functioning (p < 0.05).  Conclusion The study demonstrated that the overall QoL of TS participants was good and almost similar to that of the controls. However, TS group had significantly lower scores for social domain and had greater concerns in social interactions, thus affecting their social life.